2020
DOI: 10.1590/s0004-2803.202000000-83
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta-analysis: lubiprostone efficacy on the treatment of patients with constipation

Abstract: BACKGROUND: Lubiprostone is a type 2 chloride channel activator that has been shown to be efficacious and safe in the treatment for chronic constipation. OBJECTIVE: To systematically review randomized clinical trials (RCTs) assessing efficacy of lubiprostone for patients with chronic idiopathic constipation (CIC), irritable bowel syndrome with predominant constipation (IBS-C) and opioid-induced constipation (OIC). METHODS: Searches were conducted in PubMed, LILACS, Cochrane Collaboration Database, and Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
1
0
1
Order By: Relevance
“…In the current study, lubiprostone significantly improved SBM frequency versus placebo (MD: 3.64); however, the results must be interpreted with caution due to the substantial heterogeneity (I 2 = 82%) between trails. An MA conducted by Passos et al also reported similar results, although it was conducted for different outcomes, such as the weekly responder rate and the SBM rate within 24 h [ 48 ]. The most common AE associated with lubiprostone was nausea, followed by abdominal bloating, headache, abdominal pain, diarrhea, and vomiting.…”
Section: Discussionmentioning
confidence: 93%
“…In the current study, lubiprostone significantly improved SBM frequency versus placebo (MD: 3.64); however, the results must be interpreted with caution due to the substantial heterogeneity (I 2 = 82%) between trails. An MA conducted by Passos et al also reported similar results, although it was conducted for different outcomes, such as the weekly responder rate and the SBM rate within 24 h [ 48 ]. The most common AE associated with lubiprostone was nausea, followed by abdominal bloating, headache, abdominal pain, diarrhea, and vomiting.…”
Section: Discussionmentioning
confidence: 93%
“…Em contrapartida, a ingestão de fibras é muito indicada para pacientes que sofrem de constipação, os quais podem se beneficiar em termos de frequência evacuatória, quando associada a ingestão de água e exercícios físicos. Ademais, auxilia em casos de diarreia controlando o peristaltismo intestinal, sendo muito benéfico também o monitoramento dos hábitos alimentares antes de fazer recomendações (Lopes et al, 2019) (Passos et al, 2020).…”
Section: Discussionunclassified
“…The efficacy of lubiprostone for CC was reported in a systematic review and meta-analysis. 30 The main adverse effects of lubiprostone include diarrhea, which is more likely in patients aged over 65 years, and nausea, which is more likely in female patients. 31 The 24-µg lubiprostone capsule was first approved in Japan, and can be used to administer the standard dose of 48ug daily, which is 24-ug twice daily.…”
Section: Treatment Of CCmentioning
confidence: 99%